Muscle Belly Gearing Positively Affects the Force–Velocity and Power–Velocity Relationships During Explosive Dynamic Contractions - Monte, Andrea; Bertucco, Matteo; Magris, Riccardo; Zamparo, Paola (Frontiers in Physiology, 2021)
Changes in muscle shape could play an important role during contraction allowing to circumvent some limits imposed by the fascicle force–velocity (F–V) and power–velocity (P–V) relationships. Indeed, during low-force high-velocity contractions, muscle belly shortening velocity could exceed muscle fascicles shortening velocity, allowing the muscles to operate at higher F–V and P–V potentials (i.e., at a higher fraction of maximal force/power in accordance to the F–V and P–V relationships). By using an ultrafast ultrasound, we investigated the role of muscle shape changes (vastus lateralis) in determining belly gearing (muscle belly velocity/fascicle velocity) and the explosive torque during explosive dynamic contractions (EDC) at angular accelerations ranging from 1000 to 4000°.s–2. By means of ultrasound and dynamometric data, the F–V and P–V relationships both for fascicles and for the muscle belly were assessed. During EDC, fascicle velocity, belly velocity, belly gearing, and knee extensors torque data were analysed from 0 to 150 ms after torque onset; the fascicles and belly F–V and P–V potentials were thus calculated for each EDC. Absolute torque decreased as a function of angular acceleration (from 80 to 71 Nm, for EDC at 1000 and 4000°.s–1, respectively), whereas fascicle velocity and belly velocity increased with angular acceleration (P < 0.001). Belly gearing increased from 1.11 to 1.23 (or EDC at 1000 and 4000°.s–1, respectively) and was positively corelated with the changes in muscle thickness and pennation angle (the changes in latter two equally contributing to belly gearing changes). For the same amount of muscle’s mechanical output (force or power), the fascicles operated at higher F–V and P–V potential than the muscle belly (e.g., P–V potential from 0.70 to 0.56 for fascicles and from 0.65 to 0.41 for the muscle belly, respectively). The present results experimentally demonstrate that belly gearing could play an important role during explosive contractions, accommodating the largest part of changes in contraction velocity and allowing the fascicle to operate at higher F–V and P–V potentials.